(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article studies the manifestation of beauty and aesthetics in the aesthetics of labor, the fact that labor is an aesthetic activity, the manifestation of aesthetics in production, in the working conditions and in the tools of labor, the role of the results of labor in the aesthetics of labor, the importance of the labor collective and its moral and aesthetic environment, the influence of the aesthetics of labor on improving the spirituality of a person, the working environment, the representation of labor in works of art and the influence of labor on the aesthetic education of young people.